Reversing the Resource Curse: Foreign Corruption Regulation and Economic Development - Hans B. Christensen; Mark Maffett; Thomas Rauter (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2020)
We examine the impact of foreign corruption regulation on economic development in highcorruption- risk areas. We find that, after a mid-2000s increase in enforcement of the US Foreign Corrupt Practices Act (FCPA), economic activity (measured by nighttime luminosity) in African communities within a 50-kilometer radius of natural resource extraction facilities subject to the FCPA increases by 8%. Local perceptions of corruption also significantly decline. Consistent with the increase in economic activity being driven, at least in part, by existing extraction firms shifting to business practices that are more beneficial to the local communities where they operate, the association between resource production and local economic activity increases by 37%. Overall, our findings suggest that anti-corruption regulation originating in developed countries is effective in changing corporate behavior and has a positive economic impact in developing countries.
Keywords: F50; F60; K2; M4; O1; 330; Foreign Corruption Regulation; Foreign Corrupt Practices Act (FCPA); Economic Development; Natural Resource Extraction